THE INFLUENCE OF CONTAINER CRANE PRODUCTIVITY AND THE SHIP CALL FREQUENCY ON THE CARGO HANDLING PERFORMANCE - Azza Aunillah; Yusmar Ardhi Hidayat; Nur Rini (Politeknik Negeri Semarang, 2015)
The purpose of this research are to analyze the influence of container crane productivity (X1)and ship call frequency (X2) on the number of containers handled (Y) at Terminal PetikemasSemarang branch PT. Pelabuhan Indonesia III. The tool of analysis which was used wasMultiple Regression with Classic Assumption Test. This research used secondary data obtainedfrom TPKS such as monthly report the achievement of performance, monthly report of ship calland monthly report of stevedoring production within period of 6.5 years (January 2009 – June2015).The Result of the Multiple Regression Analysis was Log Y = 4.923991 + 0.525387 log XI+ 0.423276 log X2 + e. This equation showed that all regression coefficients were positive. Itmeans that if container crane productivity and ship call frequency was increased, the number ofthe containers handled would increase too.β1= 0.525, it means that if there is increase in container crane productivity by 10%, it will increase the cargo handling performance by 5.25%. Next, β= 0.423, it explains that if there is an increase in ship call frequency by 10%, it willincrease the cargo handling performance by 4.23%. The result of Coefficient of Determination ofTest shows that container crane productivity and ship call frequency give the proportion orpercentage of the total variation in the number of containers handled for about 94,8%. While, FTestshows that container crane productivity and ship call frequency influenced simultaneouslyon the number of containers handled. Furthermore, container crane productivity influencedpositively on the number of containers handled. Then the other X variable, ship call frequencyinfluenced positively on the number of containers handled.2Key words: Container Crane, Ship Call, Cargo Handling and Port.